2018
DOI: 10.3390/s18124306
|View full text |Cite
|
Sign up to set email alerts
|

Lifting Wavelet Transform De-noising for Model Optimization of Vis-NIR Spectroscopy to Predict Wood Tracheid Length in Trees

Abstract: The data analysis of visible-near infrared (Vis-NIR) spectroscopy is critical for precise information extraction and prediction of fiber morphology. The objectives of this study were to discuss the de-noising of Vis-NIR spectra, taken from wood, to improve the prediction accuracy of tracheid length in Dahurian larch wood. Methods based on lifting wavelet transform (LWT) and local correlation maximization (LCM) algorithms were developed for optimal de-noising parameters and partial least squares (PLS) was emplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…LWT was used for de-noising and the optimal de-noising parameters were discussed in the prediction of wood tracheid length in our previous study [34]; the results demonstrated that LWT, as a second-generation wavelet, has more power to suppress noise and improve model performance when compared to other de-noising methods such as moving average, loess, Savitzky-Golay, and lowess. According to the advantages of LWT, the performance of models using wavelet coefficients of LWT and constructed spectra were first compared in this study.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…LWT was used for de-noising and the optimal de-noising parameters were discussed in the prediction of wood tracheid length in our previous study [34]; the results demonstrated that LWT, as a second-generation wavelet, has more power to suppress noise and improve model performance when compared to other de-noising methods such as moving average, loess, Savitzky-Golay, and lowess. According to the advantages of LWT, the performance of models using wavelet coefficients of LWT and constructed spectra were first compared in this study.…”
Section: Discussionmentioning
confidence: 94%
“…Taking density as an example, 280 wood samples from two different geographical origins belonging to three of the major commercial species (i.e., Dahurian larch, Japanese elm, Chinese white poplar) were collected for spectra collection and density estimation. The spectra were processed by lifting wavelet transform (LWT) [34], and different reconstruct means for spectra (wavelet coefficients and constructed spectra after de-noising) were also compared. The support vector machine (SVM) optimized by particle swarm optimization (PSO) was used for tracking origin and identifying species.…”
Section: Introductionmentioning
confidence: 99%
“…VIS and NIRS are suitable techniques to replace laborious and uneconomic conventional analyses, as they require no treatment of the sample, are rapid and readily assessed, and have the potential for automation and on-site application (Casson et al 2020, Santos et al 2021. In wood science, these techniques have proven useful in predicting chemical properties (Lengowski et al 2018), moisture content (Kobori et al 2013, Chen and, basic density (Li et al 2020, de Abreu Neto et al 2020, anatomical element sizes (Li et al 2018) and mechanical properties , de Abreu Neto et al 2020, as well as for identifying species (Nisgoski et al 2017). In the energy context, they are feasible for the assessment of biodiesel quality (Pilar Dorado et al 2011, Fernandes et al 2011, prediction of the heating value of manure (Preece et al 2013), and rapid determination of total petroleum hydrocarbon content (Douglas et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The R 2 values were higher than 0.85 for soluble solids content, moisture content, and pH. In the forestry field, WT (Daubechies-5, db5) and LWT (db2) were used to optimize Populus davidiana and larch spectra, respectively in our previous studies (Li et al, 2018a;Li et al, 2018b). In this study, LWT with four wavelet functions including Haar, sym3, db3, and bior1.3 were compared simultaneously among various tree species from two locations.…”
Section: Discussionmentioning
confidence: 97%